1977
DOI: 10.2172/7260003
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-type model of the global carbon cycle for the estimation of dose to the world population from releases of carbon-14 to the atmosphere

Abstract: It is a pleasure to recognize the contributions of a nuaber of individuals to the work described in this document and to the preparation of the report itself. All are staff members of Oak Fidge National Laboratory. M. F.. Emanuel, C. F. Baes, Jr., and A. R. Olsen served as technical reviewers and suggested a number of improvements in the manuscript. C. C. Travis also read the manuscript and provided oral comments. Special thanks are due J. S. Olson for his continuing interest in t*ie work and for his regular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The vertical structure within each latitude zone is essentially described by Oeschger et al's (1975) box-diffusion model as modified by Killough (1977) and Butt and Viecelli (1980). These latter modifications include the use of model for computing mixed layer CO2 partial pressures and resulting atmosphere-ocean exchange coefficients, and the use of an energy balance climate model with ocean heat capacity for determining the temperatures used in the computation of the exchange coefficients.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The vertical structure within each latitude zone is essentially described by Oeschger et al's (1975) box-diffusion model as modified by Killough (1977) and Butt and Viecelli (1980). These latter modifications include the use of model for computing mixed layer CO2 partial pressures and resulting atmosphere-ocean exchange coefficients, and the use of an energy balance climate model with ocean heat capacity for determining the temperatures used in the computation of the exchange coefficients.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The carbon cycle is essentially the box-diffusion model initially developed by Oeschger et al (1975) and modified by Killough (1977). It consists of an atmospheric carbon pool (or box), two biosphere boxes (for slow and rapid turnover) and an ocean whose carbon distribution is governed by a diffusion equation.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Others using Keeling's equations (e.g. Hoffert et al, 1978;Killough, 1977) have fixed ocean temperature at the present global average. The details of this computation and other aspects of the CO2 model are available in Burt (1978).…”
Section: Description Of the Modelmentioning
confidence: 99%
“…A detailed description ot the calculational models and sensiflvity analysis used in this evaluation is provided in a paper by Killough (1977), where it is demonstrated that the global dose conversion factor calculated in this manner is rather insensitive to the range of parameters which could be considered applicable to defining the transport of carbon through the ecosystem. In addition, the calculated value is consistent with values reported by other investigators using different calculational techniques.…”
Section: Wash-9460mentioning
confidence: 99%